Nivel de autoeficacia en madres adolescentes y adultas en la ciudad de Quito - Vargas Ramírez, Allison Natalia (2019)
The main objective of this research is to identify the influence of age on the level of self efficacy of mothers in different ages . This study will have two groups: adolescent mothers from 13 to 17 years old and adult mothers from 18 to 45. both groups reside in Quito. It´s important to analice the concept of maternity from a socio-cultural and biological perspective to define the consequences of this process in mothers with different age ranges and the challenges that motherhood brings. In order to obtain results, it is important to evaluate the self-efficacy in mothers. Which is a as the self-referential characteristic. And also analice the demands of each evolutionary cycle. The theory is based on Bandura's contribution about the cognitive social theory. This theory explains that people learn about themselves and their capacity for performance, based on their own experiences. These experiences determine their future. In terms of methodology, this is a quantitative study, with a comparative scope and non-experimental design. To collect information we will use a sociodemographic questionnaire and the General Scale of Self-efficacy, adapted to the spanish context by Baessler and Schwarzer. These instruments are going to be applied equally in both groups. The statistical analysis will be descriptive and inferential; It will be analyzed with the Statistical Package for Social Sciences (SPSS) program, in order to compare results and determine the difference in the level of self efficacy of adolescent and adult mothers, residents of Quito.